Petilipinnis, a new genus for Corvina Grunniens Schomburgk, 1843 (Perciformes, Sciaenidae) from the amazon and essequibo river basins and redescription of Petilipinnis Grunniens - Casatti, Lilian (Papéis Avulsos de Zoologia, 2002)
Petilipinnis, newgenus, is proposed for Corvina Schomburgk, from the Amazon and Essequibo river basins. It is distinguishable from Other Sciaenidae genera with the exception of Menticirrhus, by the presence of only on espine in the analfin. From Menticirrhus, Petilipinnis differs by the morphology of the swimbladder and by the number of dorsal fin soft rays. Also a redescription of Petilipinnis grunniens is presented